Gene knockdown in malaria parasites via non-canonical RNAi - Hentzschel, Franziska; Müller, Ann-Kristin; Grimm, Dirk (Nucleic acids research, 2020)
Abstract. The lack of endogenous RNAi machinery in the malaria parasite Plasmodium hampers gene annotation and hence antimalarial drug and vaccine development.
Published online 4 November 2019
Gesehen am 09.07.2020